Ecology problem updating in Tatar literature of the 2nd-half of the 20th-century - SAYFULINA, F.S; GAFIYATOVA, E.V; HUSNUTDINOV, D.H; SAGDIEVA, R.K.; ISKAKOVA, Z.M. (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The study is a description of modern national Tatar Literature beginning with the 1970s till the present. The methods of continuous sampling, linguistic description, and the comparative method have been the tools for this research. The object of this study is the reflection of the term "forest" in the national literature. Nowadays, the irreplaceable role of forests as an ecological framework of the biosphere, the main component of natural complexes determining the stability and ecological balance on the planet, is universally recognized. In modern literature, forests are reflected as a global spiritual crisis of mankind. RESUMEN El estudio es una descripción de la literatura tártara moderna a partir de la década de 1970 hasta el presente. Los métodos de muestreo continuo, descripción lingüística y el método comparativo han sido herramientas para esta investigación. El objeto de este estudio es el reflejo del término "bosque" en la literatura nacional. Hoy en día, el papel irremplazable de los bosques como marco ecológico de la biosfera, el componente principal de los complejos naturales que determinan la estabilidad y el equilibrio ecológico en el planeta, es universalmente reconocido. En la literatura moderna, los bosques se reflejan como una crisis espiritual global de la humanidad.